Deep Neural Network with Consistency Regularization of Multi-Output Channels for Improved Tumor Detection and Delineation - Seo, Hyun seok; Yu, Lequan; Ren, Hongyi; Li, Xiaomeng; Shen, Liyue; Xing, Lei (Institute of Electrical and Electronics Engineers Inc., 2021)
Deep learning is becoming an indispensable tool for imaging applications, such as image segmentation, classification, and detection. In this work, we reformulate a standard deep learning problem into a new neural network architecture with multi-output channels, which reflects different facets of the objective, and apply the deep neural network to improve the performance of image segmentation. By adding one or more interrelated auxiliary-output channels, we impose an effective consistency regularization for the main task of pixelated classification (i.e., image segmentation). Specifically, multi-output-channel consistency regularization is realized by residual learning via additive paths that connect main-output channel and auxiliary-output channels in the network. The method is evaluated on the detection and delineation of lung and liver tumors with public data. The results clearly show that multi-output-channel consistency implemented by residual learning improves the standard deep neural network. The proposed framework is quite broad and should find widespread applications in various deep learning problems. IEEE